The Influence of Enterprise Online Information Behavior on Consumer Satisfaction - Liang, Liu (ABAC ODI JOURNAL Vision. Action. Outcome, 2021)
Based on findings from previous studies a model of the influence of enterprise online information behavior on consumer behaviors was formulated, analyzed, and developed using data collected by questionnaire from a sample of 479 consumers in the context of China. Enterprise behavior is represented by three constructs (information disclosure, interaction, and utilization) which influence consumer behaviors related to perceptions of pleasure, control, and attention and in turn consumer satisfaction. Many of the findings related to direct effects that have been reported in previous studies conducted in the context of western societies were confirmed. However, there were new findings related to significant direct, indirect, and total effects on consumer satisfaction due to information disclosure, interaction, and utilization. Apart from the theoretical contribution of the study, especially the analysis of indirect and total effects, there were practical implications. These are discussed with the objective of improving enterprise online behaviors with positive consequences for consumer behaviors and especially for improved consumer satisfaction. Importantly, the study addresses the limited number of previous studies conducted with Chinese consumers in online environments in China.